Implementation Of Gadget Use On Students' Social Behavi Or And Learning Effectiveness In Schools (Study at Arrasyadiyah Vocational School, Serang City) - Zohriah, Anis; Sobihah, Hani; Gunawan, Agus; Fauzi, Anis; Anurogo, Dito (Yayasan Cendekia Gagayunan Indonesia, 2025)
This study investigates the implementation of gadget use on social behavior and learning effectiveness of students at SMK Arrasyadiyah, Serang City. Along with the development of digital technology, the use of gadgets among students is increasingly widespread, including its use as a learning tool, entertainment, and social communication. This study aims to analyze the impact of gadget use on social behavior and learning effectiveness of students through a qualitative approach. Data collection methods include observation and in-depth interviews with students, teachers, and schools. The results of the study show a dual impact of gadget use. Positively, gadgets increase students' access to information and expand their social networks. However, negatively, excessive gadget use can reduce direct social interaction, decrease interpersonal communication skills, and disrupt focus and concentration in learning. Furthermore, this study highlights the importance of managing gadget use wisely. The role of teachers and parents is crucial in guiding students to use gadgets for academic purposes without sacrificing their social interactions.Therefore, this study recommends the development of school policies that regulate the use of gadgets in learning. This policy is expected to maximize the benefits of technology while minimizing the negative impacts on students' social and academic development. Thus, students can utilize technology optimally to support their learning process without ignoring the importance of healthy social interactions.